A Framework for Creation of Linked Data Mashups - A Case Study on Healthcare - Lopes, Gabriel; Vidal, Vânia Maria P.; Oliveira, Mauro (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
Linked Data promotes the publication of structured data on the Web, easing the development of an homogeneized-view over heterogeneous sources, called Linked Data Mashup view (LDM view). But the development of this homogeneizedview still is a challenging task. This article proposes a framework Ontology-based that aims to ease the process of creation of LDM views. This framework allow users without specifics knowledge to create their own applications, based on their needs. We also present a case study in which we use our approach to develop an integrated view over two heterogeneous sources from Brazilian Public Health System.